SOCIALLY VULNERABLE GROUPS - State Planning Board, Government of Kerala
In terms of literacy, life expectancy, and mean age at marriage, women in Kerala score higher than any other state in the country. Still, incidence of crimes against women, rape, and sexual harassment is high in Kerala; female health issues have assumed alarming dimensions; autonomy of women in household matters; and their participation in economic activities is low. Kerala is in the midst of a unique and irreversible process of demographic transition that has resulted into enlarged elderly population. In case of disability, according to the figures based on the 2001 Census, 2.7 per cent of State's population is disabled. And, lastly Kerala has a long history of in-migration from other states which become minorities. So, there have been signs of dissatisfaction emerging in the state, due to the absence of institutionalized efforts. The strategies must involve not a mere alleviation of circumstances, but rather, a careful analysis of different vulnerabilities, how these can be prevented or diffused, and in general, the levels of social infrastructure that must be established for enhancing the quality of life for them. Mainstreaming of concerns of socially vulnerable groups are needed to alleviate their concerns. In urbanisation, infrastructure development, their concerns have been taken into account while designing urban spaces or infrastructure.